Cosmic Ray Neutron Soil Moisture Estimation Using Physically Based Site‐Specific Conversion Functions. Issue 11 (31st October 2020) - Andreasen, Mie; Jensen, Karsten H.; Bogena, Heye; Desilets, Darin; Zreda, Marek; Looms, Majken C.
Abstract: In order to advance the use of the cosmic ray neutrons (CRNs) to map soil moisture in heterogeneous landscapes, we need to develop a methodology that reliably estimates soil moisture without having to collect 100+ soil samples for each point along the survey route. In this study, such an approach is developed using physically based modeling with the numerical MCNP neutron transport code. The objective is to determine site‐specific conversion functions to estimate soil moisture from CRNs for the dominant land covers. Here, we assess this methodology at three field sites with similar mineral soil composition, but different land covers. First, we ensure that the developed models capture the most important differences in neutron transport behavior across sites. For this, we use measured time series and height profiles of thermal and epithermal neutrons. Then, we compare the estimates obtained from the site‐specific conversion functions with the standard N 0 ‐calibration function. Finally, we compare the CRN soil moisture estimates with independent soil moisture estimates. Overall, the site‐specific models are in agreement with the observed trends in neutron intensities. The site‐specific soil moisture is similar to the N 0 ‐estimated soil moisture, which results in comparable statistical measures. We show that various land covers have a significant impact on the amount and soil moisture sensitivity of epithermal neutrons, while the thermal neutrons are affected to a less degree. Thereby, thermal‐to‐epithermal neutron ratios can be used to identify the land cover type and thereby the appropriate conversion function for soil moisture estimation for each point along the survey route. Key Points: CRN soil moisture can be estimated without calibration using oven‐dried samples The proposed soil moisture conversion functions are dependent on the land cover type The land cover type can be determined from the thermal‐to‐epithermal neutron ratio